Implementasi Metode FIFO pada Sistem Pendaftaran dan Antrian Pasien pada FX Dental Clinic Berbasis Web - Rindiyani; Zakaria, Hadi (shofanah Media Berkah, 2023)
FX Dental Clinic is a health clinic that provides individual dental health services that provide basic dental services and treatments. In general, clinics only use paper to record patient registration so that it can be presented incompletely and inaccurately. Patient registration and doctor schedules at FX Dental Clinic are still not effective because the system used is incomplete so that patient schedules often collide/clash with other patients, which can affect speed and less than optimal medical services required if the registration activities can be fulfilled with availability. tools that can make work easier, one of which uses computerization. To overcome this problem, the author conducted research using the FIFO method to create a system at FX Dental Clinic that helps patients, Admin and doctors to make patient registration more focused. The system created is a web-based system. The method for developing the patient registration and queue system at FX Dental Clinic uses the FIFO (first in first out) method using ERD (Entity Relationship Diagram) and LRS (Logical Record Structure) design. Program implementation uses the PHP programming language with a database using MySQL. And the author uses RAD in creating the design flow. It is hoped that creating a web-based patient registration and queue system application can make it easier for patients, along with FX Dental Clinic Admin, to assist with the patient registration process. So that patients are more focused in registering.